Relationship Between Worker Age And Work Shifts With Work Fatigue Among Security Guards At Pt. Pertamina Geothermal Energy Area Lahendong - Noeroel Widajati; Paul Kawatu; Graserio Barahamin (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Work fatigue is a major occupational health and safety concern because it increases the risk of work-related accidents and decreases overall performance. Fatigue is a complex condition that includes not only physical and psychological exhaustion but also reduced physical performance, feelings of tiredness, decreased motivation, and lower work productivity. Many factors can influence work fatigue, such as individual characteristics including age, gender, length of service, and nutritional status, as well as job-related factors like workload, work environment, and working time arrangements, particularly shift work. This study aimed to determine the relationship between worker age and work shifts with work fatigue among security personnel at PT Pertamina Geothermal Energy Lahendong Area. The research used a quantitative approach with an analytic observational design and applied a cross-sectional study method. Data collection was carried out in June 2023 involving 71 security workers as respondents.Statistical analysis was conducted to examine the correlation between age and work fatigue and between work shifts and work fatigue. The results showed that there was no significant relationship between age and work fatigue, indicated by a p-value of 0,640. Similarly, the analysis of work shifts and fatigue showed no statistically significant relationship, with a p-value of 0,082. Although the correlation coefficient for work shifts and fatigue was 0.496, no significant association, the result did not reach statistical significance.In conclusion, this study found that worker age and work shift were not significantly associated with work fatigue among security workers at PT Pertamina Geothermal Energy Lahendong Area overall.